Giant orbital Hall effect due to the bulk states of 3D topological insulators - James H. Cullen; Hong Liu; Dimitrie Culcer (npj Spintronics)
Abstract The highly efficient torques generated by 3D topological insulators make them a favourable platform for faster and more efficient magnetic memory devices. Recently, research into harnessing orbital angular momentum in orbital torques has received significant attention. Here we study the orbital Hall effect in topological insulators. We find that the bulk states give rise to a sizeable orbital Hall effect that is up to 3 orders of magnitude larger than the spin Hall effect in topological insulators. This is partially because the orbital angular momentum that each conduction electron carries is up to an order of magnitude larger than the ℏ/2 carried by its spin. Our results imply that the large torques measured in topological insulator/ferromagnet devices can be further enhanced through careful engineering of the heterostructure to optimise orbital-to-spin conversion.